STUDI DESKRIPTIF KELOMPOK RISIKO WANITA USIA SUBUR DI WILAYAH KERJA UPT PUSKESMAS GUNTUNG - Hartuti, Hartuti; Dewi Iswandari, Novita; Fajriannor TM, M. (Midwifery And Complementary Care, 2024)
Background: Women of Reproductive Age (WRA) are defined by the Ministry of Health of the Republic of Indonesia as women between the ages of 15 and 49. Women in this age group fall into the "4 Too" risk category when pregnant. The "4 Too" conditions refer to giving birth too young, too often, too close in spacing, and too old. Objective: To identify the risk group of Women of Reproductive Age in the working area of the Guntung Community Health Center (UPT Puskesmas Guntung). Method: This research used a descriptive method with a sample of 113 Women of Reproductive Age who visited the Guntung Health Center. The sample was taken using a total sampling technique. Results: Women of Reproductive Age in the Guntung Health Center working area showed the following distribution based on the "4 Too" risks: Too young (<20 years old) 29 women (26%), Too old (>35 years old) 34 women (30%), Multiparous (≥2 children) 23 women (29%), Too close spacing between births 22 women (19%), Chronic illness (Hypertension) 25 women (22%), Chronic illness (Anemia) 20 women (18%) Conclusion: The risk groups among Women of Reproductive Age in the Guntung Health Center working area fall into the "4 Too" categories, Too young (<20 years) 29 women, Too old (>35 years) 34 women, Multiparous (≥2 children) 23 women, Too close in spacing 22 women, In addition, 25 women had chronic illnesses such as Hypertension, and 20 women had Anemia. Keywords: Risk group, Women of reproductive age, Chronic disease